2011
DOI: 10.1037/a0022123
|View full text |Cite
|
Sign up to set email alerts
|

Trauma reactivity, avoidant coping, and PTSD symptoms: A moderating relationship?

Abstract: In the immediate aftermath of a traumatic event, many individuals experience physiological reactivity in response to reminders of the traumatic event that typically lessens over time. However, an overreliance on avoidant coping strategies may interfere with the natural recovery process, particularly for those who are highly reactive to trauma reminders. In the current investigation, we examined avoidant coping as a moderator of the association between heart rate reactivity to a trauma monologue measured shortl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(112 citation statements)
references
References 24 publications
7
100
3
2
Order By: Relevance
“…This finding was contrary to our hypothesis and to a prior study which found a greater likelihood of sexual trauma among individuals with PTSD and dissociative symptoms than those with only PTSD (Wolf et al, 2012b), but is consistent with findings from the WHO World Mental Health Surveys (Stein et al, 2013). It may be that an individual's response and ability to cope with a potentially traumatic event has a larger role in determining the development of dissociative symptoms than the type of trauma per se (Pineles et al, 2011;Solomon et al, 1988). But further research is needed to evaluate the effect of type of trauma on dissociative symptoms in PTSD, including measures assessing the degree of trauma exposure for different trauma events.…”
Section: Any Dissociative Symptom Depersonalization a Derealization Bcontrasting
confidence: 67%
“…This finding was contrary to our hypothesis and to a prior study which found a greater likelihood of sexual trauma among individuals with PTSD and dissociative symptoms than those with only PTSD (Wolf et al, 2012b), but is consistent with findings from the WHO World Mental Health Surveys (Stein et al, 2013). It may be that an individual's response and ability to cope with a potentially traumatic event has a larger role in determining the development of dissociative symptoms than the type of trauma per se (Pineles et al, 2011;Solomon et al, 1988). But further research is needed to evaluate the effect of type of trauma on dissociative symptoms in PTSD, including measures assessing the degree of trauma exposure for different trauma events.…”
Section: Any Dissociative Symptom Depersonalization a Derealization Bcontrasting
confidence: 67%
“…Caregivers who spend more time diverting their thinking away from oesophageal cancer report more symptoms of both depression and anxiety [14]. Furthermore, research investigating avoidant coping and PTSD in other groups has found that the use of avoidant coping strategies prevents recovery from the disorder and is associated with increased symptom severity over time [36,37]. This is likely because avoidant coping strategies prevent anything from being done to actively manage a stressor and can result in a paradoxical increase in intrusive thoughts [30].…”
Section: Discussionmentioning
confidence: 99%
“…Asimismo, Pineles et al (2011) plantean que los individuos relativamente muy dependientes de las estrategias de afrontamiento de evitación y relativamente muy reactivos a los recuerdos del trauma pueden estar en mayor riesgo de mantener o incrementar potencialmente los síntomas de estrés postraumático en los primeros meses después del trauma.…”
Section: Estrategias De Afrontamientounclassified